Constipation: An overlooked, unmanaged symptom of patients with pheochromocytoma and sympathetic paraganglioma (2015)
ABSTRACT: Objective: Pheochromocytomas (PHs) and sympathetic paragangliomas (PGs) are tumors that produce catecholamines, predisposing patients to cardiovascular disease and gastrointestinal effects such as constipation. Objectives: i) determine the prevalence of constipation, its risk factors, and its impact on survival; ii) identify whether a systematic combination of fiber, water, and laxatives was effective for treatment of constipation. Design and methods: We retrospectively studied 396 patients with PH/PG diagnosed in 2005–2014. The study population was patients with constipation as a presenting symptom; the control group was patients without constipation as a presenting symptom. The MD Anderson Symptom Inventory was used to assess constipation and quality of life. Results: Twenty-three patients (6%) had constipation. Constipation was associated with headaches, palpitations, diaphoresis, weight loss, and excessive noradrenaline production (P!0.0001). Eighteen of these patients had non-metastatic primary tumors larger than 5 cm and/or extensive metastases. No statistically significant differences in age, sex, and genotype were noted between the study and control groups. In patients without metastases, resection of the primary tumor led to symptom disappearance. A systematic combination of fiber, water, and laxatives was associated with symptom improvement. Two patients who presented unmanaged constipation died because of sepsis from toxic megacolon. Conclusions: Constipation is a rare and potentially lethal complication in patients with PH/PGs. Severe constipation can be prevented by recognizing and treating mild symptoms